Perceived Difficulty of Iʿrāb and Students’ Motivation in Nahwu Learning - Yusriyah, Yusriyah; Hilmy, Baso; Khaerunnisa, Khaerunnisa (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Purpose – This article aims to examine students’ perceptions of the level of difficulty of I‘rāb and to analyze its impact on their motivation to learn Nahwu by considering the cognitive and affective dimensions involved in the learning process. Design/Methodology/Approach – This study employed a qualitative descriptive approach, with data collected through an open-ended questionnaire. The sample consisted of 39 undergraduate students of the Arabic Language Education program, selected using purposive sampling based on their experience in studying I‘rāb. The data were analyzed thematically through data reduction, categorization, and conclusion drawing to obtain a comprehensive understanding of students’ learning experiences. Findings – The findings indicate that most students perceive I‘rāb as a difficult subject due to the complexity of grammatical rules, the abstract nature of syntactic concepts, and the high demands of sentence structure analysis. These perceptions are closely linked to cognitive challenges and emotional responses, such as doubt and anxiety. Nevertheless, the difficulty of I‘rāb was also found to function as a challenge-based motivator for some students. Research Limitation/Implications – This study is limited by the scope of respondents and its focus on a single institutional context. However, the findings offer important implications for developing adaptive Nahwu teaching strategies that balance cognitive demands and affective support.